2021
DOI: 10.1080/21556660.2021.1989194
|View full text |Cite
|
Sign up to set email alerts
|

Denosumab improves glucose parameters in patients with impaired glucose tolerance: a systematic review and meta-analysis

Abstract: All data generated or analyzed during this study are included in this published article and its supplementary information files.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…[ 37,38 ] For example, bone morphogenic proteins derived from the bone matrix and osteoprotegerin secreted by osteoblasts have been shown to regulate insulin secretion. [ 39,40 ] Observational studies examining the effect of denosumab on glucose parameter improvement [ 41 ] and T2DM risk reduction [ 42 ] also support osteoprotegerin may play a role in mediating the relationship, but there has not been a clinical trial on denosumab with glycemic traits as the intended outcome in those with diabetes. Considering the intricate interplay between bone and glucose metabolism, depicting a complete picture of the crosstalk between these two systems is challenging and requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…[ 37,38 ] For example, bone morphogenic proteins derived from the bone matrix and osteoprotegerin secreted by osteoblasts have been shown to regulate insulin secretion. [ 39,40 ] Observational studies examining the effect of denosumab on glucose parameter improvement [ 41 ] and T2DM risk reduction [ 42 ] also support osteoprotegerin may play a role in mediating the relationship, but there has not been a clinical trial on denosumab with glycemic traits as the intended outcome in those with diabetes. Considering the intricate interplay between bone and glucose metabolism, depicting a complete picture of the crosstalk between these two systems is challenging and requires further research.…”
Section: Discussionmentioning
confidence: 99%
“… 59 Notably, although some studies did not find the clinical effect of Dmab on glucose metabolism, they detected that it seems to improve hepatic insulin sensitivity. 28 , 60 In 2021, to determine whether Dmab can improve glycemic parameters, Pacheco-Soto et al 61 did a meta-analysis involving 1203 participants and found that Dmab could reduce FPG levels (standardized mean difference, SMD = −0.388 mg/dl, p = 0.017) and ameliorate insulin resistance (HOMA-IR: −0.223, p = 0.008) in the overall population, but without the change of HbA1c (SMD = −0.075%, p = 0.538). Further subgroup analysis showed that this beneficial effect on FPG (SMD = −0.636 mg/dl, p = 0.010) and insulin resistance (HOMA-IR: −0.573, p = 0.008) was more prominent in individuals with prediabetes or diabetes than in those with NGT, and the significant improvement of HbA1c (SMD = −0.292%, p < 0.005) can also be seen.…”
Section: Dmab and Glucose Metabolismmentioning
confidence: 99%
“…Further subgroup analysis showed that this beneficial effect on FPG (SMD = −0.636 mg/dl, p = 0.010) and insulin resistance (HOMA-IR: −0.573, p = 0.008) was more prominent in individuals with prediabetes or diabetes than in those with NGT, and the significant improvement of HbA1c (SMD = −0.292%, p < 0.005) can also be seen. 61 However, there existed a relatively large heterogeneity across studies, which may affect the strength of the results. In brief, the current studies on Dmab and glucose metabolism are limited with relatively small sample sizes, variable study populations and follow-up times, and a lack of high-quality RCTs.…”
Section: Dmab and Glucose Metabolismmentioning
confidence: 99%
“…Recent studies have suggested an association between bone health and glucose metabolism, with denosumab, an antiresorptive medication in the treatment of osteoporosis, showing potential for improving insulin sensitivity and glucose tolerance . However, while some clinical evidence suggests denosumab may be positively associated with glycemic parameters, such as fasting plasma glucose and homeostatic model assessment for insulin resistance, its effect on reducing diabetes risk remains unclear . A previous post hoc analysis of the FREEDOM trial indicated no statistically significant effect of denosumab in lowering diabetes risk, but limitations due to potential issues of being underpowered and having a small number of diabetes cases make the findings of the trial inconclusive .…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 However, while some clinical evidence suggests denosumab may be positively associated with glycemic parameters, such as fasting plasma glucose and homeostatic model assessment for insulin resistance, its effect on reducing diabetes risk remains unclear. 13 A previous post hoc analysis of the FREEDOM trial indicated no statistically significant effect of denosumab in lowering diabetes risk, 14 but limitations due to potential issues of being underpowered and having a small number of diabetes cases make the findings of the trial inconclusive. 14 , 15 In contrast, a recent retrospective cohort study in the UK suggested lower diabetes risk associated with denosumab use compared with bisphosphonate use, despite potential confounding bias by indication.…”
Section: Introductionmentioning
confidence: 99%